ANALISIS KESULITAN BELAJAR SISWA SMP PADA MATERI BANGUN DATAR - Zaeri, Annisah; Leja, Ertha Agnia Maulina; Fajriah, Khadijatul; Angraini, Lilis Marina (EDUPEDIA PUBLISHER, 2024)
Purpose: This research aims to analyze the difficulties experienced by junior high school students with two-dimensional space concepts. Methodology: This quantitative research employs a descriptive approach. The subjects were 30 seventh-grade students at Pekanbaru Da'wah Middle School, Indonesia. The research object is the students' test results regarding the concept of two-dimensional space. Data collection involved asking students to complete essay test questions. Findings: The results show that 50% of students had difficulty with the indicator